Echocardiographic assessment of aortic regurgitation: a practical guideline from the British Society of Echocardiography - Kelly Victor; Liam Ring; Vasiliki Tsampasian; David Oxborough; Sanjeev Bhattacharyya; Rebecca T. Hahn (Echo Research and Practice)
Abstract Aortic regurgitation is the third most common valve lesion with increasing prevalence secondary to an ageing population. Transthoracic echocardiography plays a vital role in the identification and assessment of aortic regurgitation and proves essential in monitoring severity and determining the timing of intervention. Building on the foundations of previous British Society of Echocardiography (BSE) recommendations, this BSE guideline presents an update on how to approach an echocardiographic assessment of aortic regurgitation. It provides a practical, step-by-step guide to facilitate a comprehensive, high-quality echocardiographic assessment of aortic regurgitation. It discusses commonly encountered echocardiography-based challenges with suggestions regarding how this information is relevant in the interpretation and grading of regurgitation severity. Additionally, the value of other cardiac imaging modalities is discussed. The guideline concludes with an overview of aortic regurgitation in the clinical context, addressing chronic versus acute aortic regurgitation, which features prompt referral for intervention, and the consequences of combined valve disease.